Contraception across the transmasculine spectrum - Krempasky, Chance; Harris, Miles; Abern, Lauren; Grimstad, Frances (American journal of obstetrics and gynecology, 2020)
The field of transgender health continues to expand rapidly, including research in the area of family planning. While much attention has been given to fertility preservation and the parenting intentions of transgender individuals, far less has been paid to pregnancy prevention and contraceptive needs of people along the transmasculine gender spectrum (transgender men and gender-nonbinary persons who were assigned female at birth). Existing research illustrates that many clinicians and transmasculine individuals falsely believe that there is no risk of pregnancy while amenorrheic. These studies also show inconsistent counseling practices provided to transmasculine persons surrounding contraception and pregnancy while falling short of providing robust clinical guidance for improvement. Clinicians report a lack of adequate training in transgender reproductive health, and consequently, many do not feel comfortable treating transgender patients. The aim of this publication is to consolidate the findings of these prior studies and build upon them to offer comprehensive clinical guidance for managing contraception in transmasculine patients. To do so, it reviews the physiologic effects of testosterone on the sex steroid axis and current understanding of why ovulation and pregnancy may still occur while amenorrheic. Gender-inclusive terminology and a suggested script for eliciting a gender-affirming sexual history are offered. Common concerns (such as the effects on gender dysphoria and gender affirmation) and side effects of available contraceptive methods are subsequently addressed and how these may have a unique impact on transmasculine persons as compared with cisgender women. Lastly, a model is provided for approaching contraceptive counseling in the transmasculine population to assist clinicians and patients in determining the need for and selection of the type of contraception. To center transmasculine voices, the development of this publication’s guidelines have been led by reproductive care clinicians of transgender experience.